Islamic Law as Islamic Ethics - Reinhart, A. Kevin (Journal of religious ethics, 1983)
After arguing that Islamic law is more asic to Islamic ethics than is either Islamic theology or philosophy, the author analyzes three basic terms associated with law (and therefore ethics): fiqh, shar', and sharīah. He then sets forth the four roots (uṣūl) of legal/ethical understanding (fiqh), describes the manner in which a judgment (ḥukm) is reached in any particular case, discusses the taxonomy of such judgments, and concludes with some comments on the rela- tion within Islamic law and ethics of knowledge to action.